An assessment of periphyton mats using CHEMTAX and traditional methods to evaluate the seasonal dynamic in post-mining lakes - Konopáčová, Eliška; Schagerl, Michael; Besta, Tomas; Capkova, Katerina; Pouzar, Miloslav; Stenclova, Lenka; Rehakova, Klara (Springer, 2023)
"This study evaluated periphyton biomass, nutrient content, and taxonomical composition in three nutrient-poor post-mining lakes in the Czech Republic. Two methods, microscopy and chemotaxonomy, were used to determine the taxonomical composition of autotrophs. Both methods identified diatoms, Chlorophyta, and Cyanobacteria as the dominant groups across the lakes. Considerable congruence of the taxonomical methods was found for diatoms and Chlorophyta, however results for Cyanobacteria showed poor correlation. The differences in periphyton features among the lakes were mostly explained by the lake age and trophy. Moreover, high amounts of overwintering biomass show that periphyton development is not established ""de novo"" each year but its current stage is a cumulative result of previous years. Beside the lake age and trophy, limnological characteristics such as Si or Mg2+ also affect periphyton taxonomical composition. No correlation of periphytic C:N:P molar ratios with lake water nitrogen and phosphorus, suggests role of additional process to the nutrient uptake, likely internal nutrient recycling in periphyton. These findings are essential in predicting further succession in the examined post-mining lakes and serve as a model for newly formed lakes. As more lakes will be formed within the post-mining recultivation in the short horizon, our study contributes to their successful management."
Využití nástroje CHEMTAX a tradičních metod k hodnocení sezónní dynamiky růstu perifytonu v post-těžebních jezerech
Keywords: Algal biomass; Periphyton diversity; Periphytic pigments; Recultivation; Chemotaxonomy; Oligotrophic lake; Seasonal dynamic; Biomasa řas; Rozmanitost perifytonu; Perifytické pigmenty; Rekultivace; Chemotaxonomie; Oligotrofní jezero; Sezónní dynamika